2014
DOI: 10.1186/1472-6831-14-18
|View full text |Cite
|
Sign up to set email alerts
|

Career influences among final year dental students who plan to enter private practice

Abstract: BackgroundExisting research about the influence of educational debt on students’ decision to enter general practice immediately after graduation is conflicting. Other potential factors that could affect this decision include the influence of a spouse or other family member, the importance of a mentoring dentist, and how students perceive the burden of their debt. The goal of this study was to examine the importance of debt on career decision-making while also considering the role of other influences.MethodsRes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 13 publications
4
24
0
1
Order By: Relevance
“…In this study, the percentage of graduates planning to immediately find and enter in clinical practice (60%) was higher than the percentage of graduates wishing to continue their professional education and similar to the percentage reported in other previous international studies (Okwuje, Anderson, & Valachovic, 2008;Nashleanas, McKernan, Kuthy, & Qian, 2014). I hypothesised that other influences to be significant factors predicting the probability of planning to enter practice immediately after dental school.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the percentage of graduates planning to immediately find and enter in clinical practice (60%) was higher than the percentage of graduates wishing to continue their professional education and similar to the percentage reported in other previous international studies (Okwuje, Anderson, & Valachovic, 2008;Nashleanas, McKernan, Kuthy, & Qian, 2014). I hypothesised that other influences to be significant factors predicting the probability of planning to enter practice immediately after dental school.…”
Section: Discussionsupporting
confidence: 87%
“…In terms of encouraging or supporting dentists to undertake specialist training, the rising cost of post-graduate fees allied to the impact of centralised recruitment may have an influence with just 7.5% considering annual fees in excess of £10,000 to be reasonable. Previous research in the U.S. has indicated that educational debt in excess of $100,000 was the strongest predictor of a decision to enter private practice 28 . A requirement for mentoring to ensure that students opt for specialist training due to genuine personal interest rather than financial burden has therefore been suggested in U.S. dental schools 29 Increased availability of part-time training programmes or indeed combined training within hospital and specialist practice settings may help to mitigate these financial issues, although both require significant educational and infrastructural changes if high standards of training are to be protected.…”
Section: Discussionmentioning
confidence: 92%
“…Por otro lado, el 77% de estudiantes de odontología canadienses, consideró una carrera exclusivamente en odontología general debido a éste factor; pero si la deuda educativa no fuera un aspecto relevante, sólo el 12% seguiría considerando esta área, en beneficio de la especialización odontológica (33).…”
Section: Carga De Deuda De Los Estudiantesunclassified